2018
DOI: 10.1016/j.celrep.2018.06.047
|View full text |Cite
|
Sign up to set email alerts
|

RIG-I Recognizes the 5′ Region of Dengue and Zika Virus Genomes

Abstract: The flavivirus genus comprises major human pathogens, such as Dengue (DENV) and Zika (ZIKV) viruses. RIG-I and MDA5 are key cytoplasmic pathogen recognition receptors that are implicated in detecting viral RNAs. Here, we show that RNAs that co-purified with RIG-I during DENV infection are immuno-stimulatory, whereas RNAs bound to MDA5 are not. An affinity purification method combined with next-generation sequencing (NGS) revealed that the 5' region of the DENV genome is recognized by RIG-I. No DENV RNA was bou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
100
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(105 citation statements)
references
References 35 publications
(53 reference statements)
5
100
0
Order By: Relevance
“…As previously reported, MDA5 and RIG-I can recognize long RNA fragments or dsRNAs (not triphosphorylated) and 5′-triphosphorylated or short RNA fragments, respectively [5,34]. The two PRRs were also recognized by other flaviviruses, such as Dengue virus [35,36], Zika virus [34,37], Hepatitis virus [38], Japanese encephalitis virus [35,39], West nile virus [40,41], and Avian tembusu virus [5], indicating that DTMUV may trigger the same innate immune signaling pathway as the above flaviviruses. In this study, DTMUV was sensed by PRRs in DEFs, and various immune molecules were efficiently induced.…”
Section: Discussionmentioning
confidence: 68%
“…As previously reported, MDA5 and RIG-I can recognize long RNA fragments or dsRNAs (not triphosphorylated) and 5′-triphosphorylated or short RNA fragments, respectively [5,34]. The two PRRs were also recognized by other flaviviruses, such as Dengue virus [35,36], Zika virus [34,37], Hepatitis virus [38], Japanese encephalitis virus [35,39], West nile virus [40,41], and Avian tembusu virus [5], indicating that DTMUV may trigger the same innate immune signaling pathway as the above flaviviruses. In this study, DTMUV was sensed by PRRs in DEFs, and various immune molecules were efficiently induced.…”
Section: Discussionmentioning
confidence: 68%
“…S1B). We previously reported specific viral RNA-binding profiles on RLR compared to non-specific binding (Cherry) upon MV and DV-4 infections ( 15, 16 ) (Fig. S1C-D).…”
Section: Mainmentioning
confidence: 82%
“…In this work, we specifically identified the repeat family of Y-RNAs, and in particular RNY4, as a model of endogenous RNAs whose unique structure confers a previously unknown function as RIG-I agonists. We observed a contribution of Y-RNAs in RLR signaling during infections by MV and DV-4, both RNA viruses replicating in the cytoplasm and producing RLR-specific viral RNA ligands ( 15, 16 ). MV and DV-4 are acute viral infections where the speed of host response is critical to halt and ultimately clear viral replication.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This observation was then recapitulated in various cell types (Huh7 hepatocarcinoma cells, endothelial cells, and primary monocytes) and experimental settings [17,[40][41][42]. Combining affinity purification and next-generation sequencing, Chazal and colleagues recently showed that RIG-I is able to recognize 5 -ppp uncapped DENV vRNA, suggesting that detection of DENV nucleic acids occurs before the 5 -end maturation by capping is completed and that vRNA is afterwards hidden from PRR [43]. In stark contrast, the putative role of MDA5 in the detection of DENV nucleic acids remains unclear.…”
Section: Denv Vrna-recognitionmentioning
confidence: 94%